UNDERGRADUATE STUDENTSâ€™ MISCONCEPTION ON ACID-BASE AND ARGENTOMETRIC TITRATIONS: A CHALLENGE TO IMPLEMENT MULTIPLE REPRESENTATION LEARNING MODEL WITH COGNITIVE DISSONANCE STRATEGY - Widarti, Hayuni Retno; Permanasari, Ana; Mulyani, Sri (UPI Press, 2017)
The study was conducted to map the misconception pattern of chemistry prospective teachers who learned acid-base and argentometric titration. Further, it attempts to minimize misconception through a multiple representation model of learning chemistry with cognitive dissonance strategy. The first treatment was done on acid-base titration and the second treatment on argentometric titration materials. The multiple choice test with open reasons was administered to 30 undergraduate students. The finding shows that 28.6% students have the same pattern of misconception while learning in both of the courses. After the treatment, misconception decreased to 9.5% on the first treatment, and 9.4% on the second treatment. The model was found to be suitable to decrease the misconception, but could not change the misconception into â€œzero misconceptionâ€, especially for microscopic and symbolic representations.